Genetic factors of cervical spondylotic myelopathy-a systemic review. (October 2017) - Wang, Guohua; Cao, Yong; Wu, Tianding; Duan, Chunyue; Wu, Jianhuang; Hu, Jianzhong; Lu, Hongbin
Highlights: The polymorphisms of 6 genes were associated with CSM. The polymorphisms of 3 genes were associated with the postoperative outcome. The polymorphism of BDNF, VDR, and expression of COX-2 were associated with the severity of disease. Abstract: Background: Cervical spondylotic myelopathy (CSM) is a degenerative disorder of the neck. Recent studies have reported the roles of single nucleotide polymorphisms and abnormal gene expression in the etiology and development of CSM. However, a systemic review of these findings is currently unavailable. Methods: A systemic review of genetic factors of CSM was conducted through searching PubMed and EMbase databases. A total of 9 studies were included in this study, which included 8 genes: brain derived neurotrophic factor (BDNF), osteopontin (OPN), bone morphogenic protein (BMP) 4, collagen IX, vitamin D receptor (VDR), apolipoprotein E (ApoE), hypoxia-inducible factor α (HIF-1α), and cyclooxygenase 2 (COX-2). Results: The polymorphisms of 6 genes (OPN, BMP-4, collagen IX, VDR, HIF-1α) showed significant association with the susceptibility to or risk of CSM. The polymorphisms of 3 genes (BMP-4, ApoE4, HIF-1α) were significantly associated with the postoperative outcome. The polymorphism of BDNF, VDR, and expression of COX-2 were associated with the severity of disease. Conclusion: This review demonstrates that 8 genes were associated with CSM although there is no repeated study. This review also suggests that large scale and high quality studies are needed to provide more reliable evidence for future evaluation.